The Plant Ionome Revisited by the Nutrient Balance Concept - Parent, Serge-Étienne; Parent, Leon Etienne; Egozcue, Juan Jose; Rozane, Danilo E.; Hernandes, Amanda; Lapointe, Line; Gentile, Valerie H.; Naess, Kristine; Marchand, Sebastien; Lafond, Jean; Mattos Jr, Dirceu; Barlow, Philip; et al. (Frontiers in Plant Science, 2013)
Tissue analysis is commonly used in ecology and agronomy to portray plant nutrient signatures. Nutrient concentration data, or ionomes, belongs to the compositional data class, i.e. multivariate data that are proportions of some whole, hence carrying important numerical properties. Statistics computed across raw or ordinary log-transformed nutrient data are intrinsically biased, hence possibly leading to wrong inferences. Our objective was to present a sound and robust approach based on a novel nutrient balance concept to classify plant ionomes. We analyzed leaf N, P, K, Ca and Mg of two wild and six domesticated fruit species from Canada, Brazil, and New Zealand sampled during reproductive stages. Nutrient concentrations were (1) analyzed without transformation, (2) ordinary log-transformed as commonly but incorrectly applied in practice (3) additive log ratio (alr) transformed as surrogate to stoichiometric rules and (4) converted to isometric log-ratios (ilr) arranged as sound nutrient balance variables. The ordinary log transformation led to biased multivariate analysis due to redundancy between interacting nutrients. The alr- and ilr-transformed data provided unbiased discriminant analyses of plant ionomes, where wild and domesticated species formed distinct groups and the ionomes of species and cultivars were differentiated without numerical bias. The ilr nutrient balance concept is preferable to alr, because the ilr technique projects the most important interactions between nutrients into a convenient Euclidean space. This novel numerical approach allows rectifying historical biases and supervising phenotypic plasticity in plant nutrition studies.